Microfluidic device performing on flow study of serial cell–cell interactions of two cell populations. Issue 70 (13th December 2019) - Duchamp, Margaux; Dahoun, Thamani; Vaillier, Clarisse; Arnaud, Marion; Bobisse, Sara; Coukos, George; Harari, Alexandre; Renaud, Philippe
Abstract : In this study we present a novel microfluidic hydrodynamic trapping device to probe the cell–cell interaction between all cell samples of two distinct populations. Abstract : In this study we present a novel microfluidic hydrodynamic trapping device to probe the cell–cell interaction between all cell samples of two distinct populations. We have exploited an hydrodynamic trapping method using microfluidics to immobilize a batch of cells from the first population at specific locations, then relied on hydrodynamic filtering principles, the flowing cells from the second cell population are placed in contact with the trapped ones, through a roll-over mechanism. The rolling cells interact with the serially trapped cells one after the other. The proposed microfluidic phenomenon was characterized with beads. We have shown the validity of our method by detecting the capacity of olfactory receptors to induce adhesion of cell doublets overexpressing these receptors. We report here the first controlled on-flow single cell resolution cell–cell interaction assay in a microfluidic device for future application in cell–cell interactions-based cell library screenings.